Pedagogical conditions for ensuring cognitive-emotional integration in medical education - Kudratova Dildor Hikmatovna (Goodwood Publishing, 2025)
Purpose: This study aims to identify and substantiate the pedagogical conditions that ensure cognitive-emotional integration in medical education, emphasizing the balance between intellectual development and emotional intelligence for the formation of empathetic, competent, and ethically responsible healthcare professionals. Methodology: A mixed-method design combining theoretical and empirical approaches was employed. The research involved 120 medical students divided equally into experimental and control groups. Data were collected using instruments such as the Mayer–Salovey–Caruso Emotional Intelligence Test (MSCEIT), Jefferson Scale of Physician Empathy (JSPE), and Reflection Questionnaire. Experimental interventions included reflection-based learning, empathy simulations, and emotionally engaging teaching strategies. Results: Findings revealed significant improvements (p < 0.05) in the experimental group in emotional intelligence (+24%), empathy (+22%), and reflective ability (+27%) compared to the control group. Qualitative data indicated enhanced motivation, emotional regulation, and professional identity formation, confirming that emotional engagement deepens cognitive understanding and ethical awareness. Conclusion: Cognitive-emotional integration effectively harmonizes rational and affective learning, strengthening both professional competence and emotional resilience. The developed pedagogical model fosters holistic development, aligning with humanistic and experiential learning theories. Limitations: The study was limited to one academic semester and a single institution, suggesting the need for longitudinal and cross-cultural validation. Contribution: This research contributes a validated pedagogical model that unites cognition and emotion, offering actionable strategies for medical educators to cultivate emotionally intelligent, reflective, and compassionate physicians.